SENSORY AND MOTOR BLOCKADES IN OBESE PATIENTS UNDERGOING UROLOGICAL SURGERY IN THE LITHOTOMY POSITION LEVELS AND DURATION OF SPINAL ANESTHESIA - Nematulloev Tukhtasin Komiljonovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Obesity significantly influences the cephalic spread of a spinal block (SB) due to decreased cerebrospinal fluid (CSF) volume. SB distribution is also affected by tissue blood flow alongside CSF dynamics. Surgical positions and techniques can alter hemodynamics, prompting us to investigate these effects during transurethral prostate resection (TUR-P) and lithotomy position (LP) in obese versus non-obese individuals. Sixty patients undergoing TUR-P under spinal anesthesia were categorized into non-obese (BMI < 25 kg/m², Group N) and obese (BMI ≥ 30 kg/m², Group O) groups. SB levels were measured post-LP at 6 and 120 minutes, with peak SB levels compared between the groups. Hemodynamic parameters were also recorded after LP. Results indicated that peak and 6-minute SB levels were comparable across both groups, but 120-minute SB levels were significantly higher in Group O (P < 0.05). Blood pressure (BP) post-LP was notably higher in Group N (P < 0.05). LP and TUR-P procedures elevated BP in Group N more than in Group O. This hemodynamic increase likely enhances spinal cord blood flow, resulting in similar SB levels in non-obese patients as observed in obese patients. However, the duration of SB may be prolonged in obese patients.